Beggary in urban India: reflections on destitution and exploitation - Sarkar, Sumita (2007)
The present paper attempts to understand beggary as a growing socio-economic problem and an extreme form of destitution and poverty in urban India. It analyses beggary from a developmental perspective and as an inevitable outcome of exploitation and criminalisation of poor under the vicious force of political economy. The present discourse further explores the possible solutions to deal with beggary under the existing Beggary Laws, the role of NGOs and of Civil Society. - Reproduced.
Keywords: Poverty - India; Poverty